Predictive factors for EGFR-tyrosine kinase inhibitor retreatment in patients with EGFR-mutated non-small-cell lung cancer – A multicenter retrospective SEQUENCE study. (February 2017) - Chang, Gee-Chen; Tseng, Chien-Hua; Hsu, Kuo-Hsuan; Yu, Chong-Jen; Yang, Cheng-Ta; Chen, Kun-Chieh; Yang, Tsung-Ying; Tseng, Jeng-Sen; Liu, Chien-Ying; Liao, Wei-Yu; Hsia, Te-Chun; Tu, Chih-Yen; et al.
Highlights: Providing clinical evidence of EGFR-TKI retreatment following chemotherapy. Survival benefit was pronounced in patients with longer drug holidays. Females with exon 21 mutation are most likely to benefit from this strategy. Abstract: Background: Acquired resistance occurs in most non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor ( EGFR) mutations experiencing a response to EGFR -tyrosine kinase inhibitor (TKI) initially. We investigated EGFR -TKI retreatment in patients who had previously received EGFR -TKI followed by chemotherapy. Materials and methods: This was a retrospective multicenter study. Patients with locally advanced or metastatic adenocarcinoma or TTF-1 (+) NSCLC, positive EGFR sensitive mutation, and EGFR -TKI reuse after initial EGFR-TKI followed by chemotherapy were enrolled. The objectives were to assess the objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) of EGFR TKI switched retreatment. Results: In total, 205 patients were enrolled, with a median age of 61.8 years (range 31.4–92.9). There was a larger proportion of females (62.9%) than males, and more never-smokers (73.2%) than ever-smokers. In the initial EGFR -TKI administration, 57.6% of patients showed a complete response (CR) or partial response (PR), and 34.6% had stable disease (SD); in the second-line chemotherapy, 13.7% had PR, and 58.0% had SD; in the EGFR -TKI retreatment, 7.3% had PR, and 37.1% had SD. The median PFS of first-line EGFR -TKI was 8.0 months (95% CI 7.3–8.2), and retreatment EGFR -TKI was 4.1 months (95% CI 2.7–4.6). The median OS since the start of the first-line EGFR -TKI therapy was 35.9 months (95% CI 28.8–50.9), and since the start of EGFR -TKI retreatment was 12.6 months (95% CI 10.4–20.9). In the univariable and multivariable regression analysis of factors associated with PFS of EGFR -TKI retreatment, time interval between the two EGFR TKIs equal to or more than 7 months was statistically significant (HR = 0.62, 95% CI 0.44-0.86; HR = 0.6, 95% CI 0.43–0.86), both p < 0.01. Females with exon 21 mutation also showed a significant difference between the two groups (HR = 0.51, 95% CI 0.30–0.86; HR = 0.52 (0.31–0.88), both p < 0.05). Conclusions: EGFR -TKI retreatment was effective in prolonging survival, and was shown to be a worthwhile option for EGFR- mutated NSCLC patients after failure of first-line EGFR -TKI and chemotherapy. The survival benefit was especially pronounced in patients with longer drug holidays from the initial EGFR -TKI and in females with the exon 21 mutation.